The Gurudharmas in Taiwanese Buddhist Nunneries - Heirman, Ann; Chiu, Tzu-Lung (Buddhist Studies Review, 2013)
According to tradition, Mahaprajapati, the Buddha’s aunt and stepmother, when allowed to join the Buddhist monastic community, accepted eight ‘fundamental rules’ (gurudharmas) that made the nuns’ order dependent upon the monks’ order. This story has given rise to much debate, in the past as well as in the present. This article first shows how the eight rules became an integrated part of the vinaya (disciplinary texts), and more particularly of the Dharmaguptakavinaya, that forms the basis of monastic ordinations in East Asia. Against the background of a much debated attack on these gurudharmas by the Taiwanese nun Shih Chao-hwei, we have then analysed the viewpoints of contemporary Taiwanese nuns, focusing on some less studied, yet very influential, Taiwanese monastic institutes. This research has brought to light a diversity of opinions on the applicability of the rules, relying in each case on a clear vision on Buddhism and vinaya.